Menschen - Leben - Vielfalt: Inklusion als Gabe und Aufgabe für Kirchengemeinden - Liedke, Ulf (Pastoraltheologie, 2012)
Humans. Life. Plurality : Inclusion as a Gift and a Challenge for the Congregation. The article presents an overview on the movement of "inclusion" as a more radical understanding and practice of integrating people with disabilities into the society. The resonances of this change with Christian theology and possible inclusive practices of congregrations are presented.